2001
DOI: 10.1046/j.1523-5394.2001.009002066.x
|View full text |Cite
|
Sign up to set email alerts
|

Problem‐Solving Cancer Care Education for Patients and Caregivers

Abstract: Most educational sessions for families affected by cancer focus on delivering information, not on building skills. These findings suggest that a one-on-one educational session that teaches problem-solving skills can be successfully delivered in a busy clinic setting. Family caregivers are especially likely to benefit from this program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
54
0
6

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 11 publications
(7 reference statements)
0
54
0
6
Order By: Relevance
“…CBIs using problem-solving skills have been shown to increase patient satisfaction with symptom control in women with recurrent and advanced breast cancer (Classen et al, 2001;Northouse et al, 2002). In addition, Bucher et al (2001) found that patients with advanced cancer in a nonrandomized clinical trial were able to improve their problem-solving ability after an educational session. Whether CBIs with a problem-solving approach affect symptom severity in patients with varying sites of cancer is unknown, however, as well as whether patients are able to maintain the skills after the intervention has ended.…”
Section: Cognitive Behavioral Interventionsmentioning
confidence: 99%
“…CBIs using problem-solving skills have been shown to increase patient satisfaction with symptom control in women with recurrent and advanced breast cancer (Classen et al, 2001;Northouse et al, 2002). In addition, Bucher et al (2001) found that patients with advanced cancer in a nonrandomized clinical trial were able to improve their problem-solving ability after an educational session. Whether CBIs with a problem-solving approach affect symptom severity in patients with varying sites of cancer is unknown, however, as well as whether patients are able to maintain the skills after the intervention has ended.…”
Section: Cognitive Behavioral Interventionsmentioning
confidence: 99%
“…atients with advanced cancer and their families experience significant distress in four domains: physical, 1,2 psychological, social, and spiritual. [3][4][5] These domains are often summarized by the term ''quality of life.''…”
mentioning
confidence: 99%
“…Las investigaciones basadas en de la terapia de solución de problemas dirigidas a cuidadores de pacientes con cáncer han reportado que tras la intervención se registran mayores niveles de conocimiento de los recursos de la comunidad y confianza en las habilidades para proporcionar cuidados a su familiar (27) un incremento en las habilidades para solucionar problemas y el tipo de estrategias empleadas, así como, el grado de bienestar emocional de los cuidadores, reducción de la tensión emocional, mayor confianza para resolver problemas, un aumento de estrategias de solución consideradas positivas tales como buscar apoyo del equipo médico (28) . Otras investigaciones han reportado que los participantes presentaron una reducción en los niveles de ansiedad, así como, un incremento de las habilidades para solucionar problemas y en la calidad de vida de los cuidadores (29) pero no de los pacientes (30) .…”
Section: Introductionunclassified